Macleod's clinical examination - Nicol, E. Fiona; Macleod, John 1915-; Robertson, Colin (Colin Ernest); Douglas, Graham (Consultant physician) (Churchill Livingstone Elsevier, 2009)
Describes the practical skills various clinicians must acquire and develop in order to evolve diagnostic procedures and management strategies and plans. This book shows you how to: talk with a patient; take the history from the patient; examine a patient; and, use investigations to support or refute your differential diagnosis.